Enhanced Path Routing with Buffer Allocation Method Using Coupling Node Selection Algorithm in MANET. (18th July 2022) - Bharti, Rajendra Kumar; S, Soundarajan; Sumant, Sushma V.; Durai, C. Anand Deva; Kumar, Relangi Anil; Singh, Kamlesh; Palivela, Hemant; Kumar, B. Rajesh; Debtera, Baru
Abstract : In a mobile network, nodes are placed in infrequent manner, which are moved along network in abruptly. Communication flaw between sender node and accepting node in path, the node having restricted energy and restricted transmission rate. It does not provide perfect route for communication among mobile nodes. It increases the packet drop rate and minimizes the lifetime of network. This work has proposed enhanced path routing with buffer allocation (IPBA) scheme which is implemented to obtain better communication; it protects the node from packet loss, and the buffer is used to maintain the temporary details of nodes and data packets that are ready to broadcast and receive. The coupling node selection algorithm is constructed to offer the path which frequently communicates data packets in normal case; the two efficient nodes are coupled with each other, and this type of nodes is selected to perform communication. It reduces the packet loss rate and increases network lifetime. End-to-end delay, communication overhead, throughput, network lifetime, packet loss, and energy consumption are the parameters considered for performance evaluations.